2013
DOI: 10.1111/eos.12104
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change of oral and general health‐related quality of life during prosthodontic treatment

Abstract: The literature presents conflicting findings on whether health-related quality of life (HRQoL) measures have sufficient evaluative properties to assess changes caused by dental interventions. The aim of our study was to compare sensitivity to change in HRQoL and OHRQoL in prosthodontic patients. In this prospective intervention study, a total of 165 consecutively recruited patients completed the Short Form-36 (SF-36) and the 49-item Oral Health Impact Profile (OHIP), as self-administered questionnaires, before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…The different OHIP versions have shown significant associations with both clinical and subjective measures of oral health (5,8,9,12). Thus, being edentulous or having few teeth, periodontitis, temporomandibular disorders/pain, and poor chewing ability have all been found to be associated with poor OHRQoL (2,3,5,8,(16)(17)(18)(19). The associations with socio-economic status (SES) have been revealed in other studies (11,14).…”
mentioning
confidence: 89%
“…The different OHIP versions have shown significant associations with both clinical and subjective measures of oral health (5,8,9,12). Thus, being edentulous or having few teeth, periodontitis, temporomandibular disorders/pain, and poor chewing ability have all been found to be associated with poor OHRQoL (2,3,5,8,(16)(17)(18)(19). The associations with socio-economic status (SES) have been revealed in other studies (11,14).…”
mentioning
confidence: 89%
“…Some studies have shown that tooth loss has an impact on general health; however, most studies indicate that measures of general health are either not sensitive enough to capture the impact of tooth loss and prosthetic restorations, or the oral status simply does not impact on self‐reported general health . The specific relationship between the location of tooth loss, prosthetic restorations and self‐reported general health has, to our knowledge, not been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, our primary null hypothesis was rejected. The OHIP summary score showed a substantial decrease after NMCD treatment, with a strong ES (0Á8) and a large change score (20 points) that were greater than those in previous studies (ES: 0Á3-0Á5, change score: 9-12 points) in the previous studies (17,(21)(22)(23) (Table S1). Furthermore, scores for all OHIP dimensions indicated an improved OHRQoL.…”
Section: Allocation Allocationmentioning
confidence: 67%
“…Table S1 Change in OHIP scores and effect size for treatment with NMCD and RPDs reported in the previous studies (17,(21)(22)(23).…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation